High Dimensional Imaging Mass Cytometry Panel to Visualize the Tumor Immune Microenvironment Contexture - Elaldi, Roxane; Hemon, Patrice; Petti, Luciana; Cosson, Estelle; Desrues, Belinda; Sudaka, Anne; Poissonnet, Gilles; Van Obberghen-Schilling, Ellen; Pers, Jacques-Olivier; Braud, Veronique M.; Anjuère, Fabienne; Meghraoui-Kheddar, Aïda (Frontiers in Immunology, 2021)
The integrative analysis of tumor immune microenvironment (TiME) components, their interactions and their microanatomical distribution is mandatory to better understand tumor progression. Imaging Mass Cytometry (IMC) is a high dimensional tissue imaging system which allows the comprehensive and multiparametric in situ exploration of tumor microenvironments at a single cell level. We describe here the design of a 39-antibody IMC panel for the staining of formalin-fixed paraffin-embedded human tumor sections. We also provide an optimized staining procedure and details of the experimental workflow. This panel deciphers the nature of immune cells, their functions and their interactions with tumor cells and cancer-associated fibroblasts as well as with other TiME structural components known to be associated with tumor progression like nerve fibers and tumor extracellular matrix proteins. This panel represents a valuable innovative and powerful tool for fundamental and clinical studies that could be used for the identification of prognostic biomarkers and mechanisms of resistance to current immunotherapies.